Results of the European Clinical Trial of Arrow CorAide Left Ventricular Assist System. Issue 2 (9th October 2012) - Saeed, Diyar; Arusoglu, Latif; Gazzoli, Fabrizio; Hetzer, Roland; Morshius, Michael; Alloni, Alessia; Viganò, Mario; Koerfer, Reiner; Golding, Leonard A. R.; El Banayosy, Aly
Abstract The aim of this study was to evaluate the safety and performance of the Arrow CorAide left ventricular assist system (LVAS) (Arrow International, Reading, PA, USA), a continuous‐flow left ventricular assist device, as bridge to transplantation or recovery as well as destination therapy in patients with New York Heart Association (NYHA) class IV heart failure. Twenty‐one patients were implanted with the CorAide LVAS between February 2005 and February 2006 in a prospective, multicenter, nonrandomized trial. Seventeen patients (81%) survived to >180 days or to transplantation. The cumulative time on device was 16.58 patient years (range 23–796 days, median 192 days). No intraoperative technical issues were observed at the time of implantation. Of the 21 implants, nine patients died on device, two were converted to other devices, and 10 were transplanted. Three patient deaths were attributed to pump polymer coating delamination. Postmortem device inspection determined delamination of the polymer coating on the pump's internal surface to be the cause of the late hemolysis and sudden fatal pump stops. No embolic or driveline infection event was recorded. The automatic flow control algorithm functioned reliably throughout the trial. Primary performance trial endpoint was achieved with 81% survival to 180 days or transplantation. Delamination of the polymer coating on the internal surface of the pump with resultant hemolysis and pump stops was the sole major device event in this trial. Elimination of the polymer coating and replacement with an amorphous carbon coating has resolved this in preclinical testing, prior to initiation of further clinical testing of this device.